Intellectual Property Law and Ethics Creating Space for Ethical Innovation from the Perspective of Dignified Justice - Kurniawan, I Gede Agus; Samsithawrati, Putu Aras; Disantara, Fradhana Putra; Nutakor, Briggs Samuel Mawunyo (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2025)
This research aims to analyze the relationship between intellectual property law and ethics in fostering ethical innovation in Indonesia from the principles of dignified justice. This study employs normative legal research methods with a conceptual approach, analyzing primary, secondary, and tertiary legal materials through literature study and qualitative analysis to examine the relationship between intellectual property law, ethics, and dignified justice in the context of innovation. The research findings indicate that the integration of ethical principles into Indonesia’s intellectual property legal framework is crucial for building a fair, inclusive, and sustainable innovation ecosystem. Intellectual Property Rights (IPR) should be seen not only as protection for exclusive rights but also as a tool to balance the interests of creators, society, and indigenous communities. Analysis of regulations and case studies such as copyright piracy, compulsory licensing in health emergencies, and protection of traditional knowledge demonstrates that ethical considerations must complement legal protections to ensure equitable access, cultural respect, and social responsibility. Adaptive legal reforms, stronger institutional enforcement, recognition of indigenous contributions, and incentives for green innovation are necessary to make Indonesia’s IPR system more humane, just, and aligned with both local wisdom and global standards.AbstrakTujuan penelitian ini adalah untuk menganalisis hubungan antara hukum kekayaan intelektual dan etika dalam mendorong inovasi yang beretika di Indonesia dalam prinsip keadilan bermartabat. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan konseptual, menganalisis bahan hukum primer, sekunder, dan tersier melalui studi kepustakaan dan analisis kualitatif untuk mengkaji hubungan antara hukum kekayaan intelektual, etika, dan keadilan bermartabat dalam konteks inovasi. Hasil penelitian menunjukkan bahwa integrasi prinsip etika dalam kerangka hukum Hak Kekayaan Intelektual (HKI) di Indonesia sangat penting untuk membangun ekosistem inovasi yang adil, inklusif, dan berkelanjutan. HKI harus dipahami bukan hanya sebagai pelindungan hak eksklusif pencipta, tetapi juga sebagai instrumen untuk menyeimbangkan kepentingan kreator, masyarakat, dan komunitas adat. Analisis terhadap berbagai regulasi dan studi kasus seperti pembajakan hak cipta, lisensi wajib dalam krisis kesehatan, serta pelindungan pengetahuan tradisional menunjukkan bahwa pertimbangan etis harus melengkapi pelindungan hukum demi memastikan akses yang adil, penghormatan budaya, dan tanggung jawab sosial. Reformasi hukum yang adaptif, penguatan lembaga penegak hukum, pengakuan terhadap kontribusi masyarakat adat, serta dorongan inovasi ramah lingkungan diperlukan agar sistem HKI Indonesia menjadi lebih manusiawi, adil, dan sejalan dengan nilai-nilai kearifan lokal dan standar global.